Creating a reflective space in higher education: The case of a Swedish course for professional principals. Issue 3 (1st December 2020) - Thelin, Katina
Abstract: This article considers the conditions, possibilities, and challenges of creating what is referred to here as a 'reflective space' within a higher education course for principals. It is informed by the findings of a qualitative research inquiry conducted in the interests of enhancing the principals' learning and professional praxis and the university educators' pedagogical praxis, within a Swedish course for school and preschool principals. Analysis of the findings highlighted two significant patterns. The first relates to the transformative benefits of creating a 'reflective space' for the principals attending the course. The second is more ambiguous and reflects their relation to and engagement with scientifically constructed knowledge. Based on these findings, the article offers considerations relevant for creating 'reflective spaces' as a means to enhance the quality of learning in higher education. Additionally, some guiding pedagogical implications are included in the final remarks.